DATABASES TO SUPPORT ASSET MANAGEMENT AND SOCIAL REUSE: THE CASE STUDY OF THE REPUBLIC OF NORTH MACEDONIA (EU and comparative law issues and challenges series (ECLIC), 2021)
Over the past decades, many EU and non EU countries have amended their legislative and institutional framework on proceeds of crime confiscation to deprive criminals of their assets more effectively and to better manage and dispose of them. There are still, however, some under-researched issues that could greatly enhance the effectiveness and efficiency of confiscation policies. A first topic is the contribution that databases can give to asset management and disposal; the second one deals with a particular asset disposal option which involves giving criminal proceeds back to the communities affected by crime and promoting their use in line with communal needs: social reuse. This article responds to this question: what is the current situation regarding these two key issues in the Republic of North Macedonia?